Additional wall attached to diaphragm wall - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for additional wall attached to diaphragm wall of Brac University new campus project.